1999
DOI: 10.1161/01.str.30.10.2197
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Dynamics of Autoregulation and Hypoperfusion

Abstract: Background and Purpose-To determine how cerebral blood flow (CBF), total and microvascular cerebral blood volume (CBV), and blood oxygenation level-dependent (BOLD) contrast change during autoregulation and hypotension using hemodynamic MRI. Methods-Using arterial spin labeling and steady-state susceptibility contrast, we measured CBF and changes in both total and microvascular CBV during hemorrhagic hypotension in the rat (nϭ9). Results-We observed CBF autoregulation for mean arterial blood pressure (MABP) be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(21 citation statements)
references
References 68 publications
1
20
0
Order By: Relevance
“…We detected no significant confounding effect of genotype on anaesthesia during fMRI as assessed by the magnitude of mean arterial blood pressure, a sensitive indicator of anaesthesia depth in rodents 43 ( P =0.17). GBR administration produced a short-lived (~8 min) blood pressure decrease (−6.0±6.3 mm Hg and −22.50±5.1 mm Hg in BTBR and B6, respectively) that was, however, well within the autoregulation window under halothane anaesthesia 44,45 and temporally uncorrelated with the fMRI responses (the latter lasting >25 min), thus arguing against a peripheral origin of the discrepant fMRI responses mapped in the two strains.…”
Section: Resultsmentioning
confidence: 92%
“…We detected no significant confounding effect of genotype on anaesthesia during fMRI as assessed by the magnitude of mean arterial blood pressure, a sensitive indicator of anaesthesia depth in rodents 43 ( P =0.17). GBR administration produced a short-lived (~8 min) blood pressure decrease (−6.0±6.3 mm Hg and −22.50±5.1 mm Hg in BTBR and B6, respectively) that was, however, well within the autoregulation window under halothane anaesthesia 44,45 and temporally uncorrelated with the fMRI responses (the latter lasting >25 min), thus arguing against a peripheral origin of the discrepant fMRI responses mapped in the two strains.…”
Section: Resultsmentioning
confidence: 92%
“…It has been shown that hemodynamic regulation is heterogeneous and that functionally induced microvascular changes can occur at small spatial scales, i.e., at the level of columns and layers (Chaigneau et al, 2003; Erinjeri and Woolsey, 2002). Laminar differences in blood volume and flow have been observed in baseline conditions as well as after stimulation, showing that blood flow regulation differs between layers and between superficial vessels and parenchyma (Choi et al, 2010; Moskalenko et al, 1998; Zaharchuk et al, 1999). Baseline blood flow and vascularization are highest in the center of the cortex (Duvernoy et al, 1981; Gerrits et al, 2000; Moskalenko et al, 1998; Weber et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…18 CBF were measured in WT mice in the following order: baseline (20 minutes), inhaled nitric oxide (40 ppm, 10 minutes), baseline (20 minutes), inhaled carbon dioxide (CO 2 , 10 minutes), and baseline (10 minutes). We used carbon dioxide (CO 2 7%, oxygen 21%, and balance nitrogen) as a positive control since carbon dioxide is known to increase CBF based on a previous report.…”
Section: Methodsmentioning
confidence: 99%